MAKSIMASI KEUNTUNGAN USAHA BUDIDAYA RUMPUT LAUT DI DESA SATHEAN - Talakua, Eygner Gerald; Pentury, Frischilla (Program Studi Agrobisnis Perikanan, Universitas Pattimura, 2017)
This study aimed to assess the maximum profit that can be obtained on seaweed cultivation in the village Sathean of Kei Kecil Subdistrict.Primary data was collected from 15 respondents through direct interviews with questionnaires and direct observation of the object studied. Date were analyzed using descriptive analysis, revenue analysis, and analysis of the allocation of production factors and maximizing profits by using linear programming. The results showed that the maximum profit that can be obtained seaweed cultivation business in the village of Sathean Kecamatan Kei Kecil is Rp 5.010.716, -. This profit is greater than the actual profit that develops today both in the peak season is only Rp 4,666,545, - and the season is less than Rp 1,717,894.